2012
DOI: 10.1097/nmd.0b013e31825bfb10
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Metacognition With Symptoms, Insight, and Neurocognition in Clinically Stable Outpatients With Schizophrenia

Abstract: Research indicates that many with schizophrenia experience deficits in metacognitive capacity or the ability to form complex representations of themselves and others. Previous work has found that metacognitive capacity in schizophrenia is correlated with symptoms, insight, and neurocognitive deficits. We sought to replicate these results in a sample of Italian participants treated in a community setting. Metacognition was assessed with the abbreviated Metacognition Assessment Scale and correlated with concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 14 publications
4
62
1
8
Order By: Relevance
“…This is in line with many earlier findings (Nicolò et al, 2012). Only the relationship between negative symptoms and understanding others is significant in this study, which is consistent with former studies in both chronic and firstepisode psychosis samples MacBeth et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in line with many earlier findings (Nicolò et al, 2012). Only the relationship between negative symptoms and understanding others is significant in this study, which is consistent with former studies in both chronic and firstepisode psychosis samples MacBeth et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…A disturbed sense of agency over thoughts can also be explained by lowered metacognitive control. The most consistent finding, however, is that low metacognition is related to more negative symptoms (MacBeth et al, 2013;Nicolò et al, 2012).…”
mentioning
confidence: 62%
“…Associations were seen between multiple metacognitive domains and cortical thickness in right rostral middle frontal gyrus and right pars triangularis, providing partial support for our second hypothesis. Inspection of MAS scores indicated that our CHR participants were more Self-Reflective, scored higher on Understanding Others, showed greater Mastery as well as higher Decentration as compared to means reported in people with schizophrenia (Lysaker et al, 2008(Lysaker et al, , 2010Nicolo et al, 2012;Macbeth et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…Social cognition includes a number of components such as Theory of Mind (ToM), Affect Recognition, and Attributional Style [53]. The second process which may be related to insight is metacognition [77][78][79][80]. Metacognition refers to activities which allow persons to be aware of and form integrated and complex ideas about the self and others.…”
Section: Deficits In Social Cognition and Poor Metacognitionmentioning
confidence: 99%